Changes in rates of violent child deaths in england and wales between 1974 and 2008. (4th April 2011) - Sidebotham, P; Atkins, B; Hutton, J
Abstract : Aims: This study used national data to determine whether or not rates of violent child deaths have fallen between 1974 and 2008. Methods: Using mortality data from the Office of National Statistics, categories that potentially contain violent child deaths were analysed for children under 1, between 1 and 14, and between 15 and 19. These data were compared with Home Office data on recorded homicides in infants aged less than 1 and children aged 1–14. Changes in death rates over time were modelled using logistic regression. Results: Rates of infant deaths registered as due to assault have fallen between 1974 and 2008 from 5.6 to 0.7 per 100 000 infants per year; those in childhood (1–14 years) have fallen from 0.6 to 0.2 per 100 000. Combining these deaths with those registered as undetermined intent, the rates are higher but still show a decline in both age groups (7.2–2.5 for male infants; 6.0–2.1 for female infants; 0.9–0.5 for boys aged 1–14 and 0.8–0.4 for girls). There is a slight fall in the rates of police recorded homicides in infants, but no observable change in the childhood rates. In adolescence, the rates of death from assault fell during the 1970s. Since then, they have remained static in young women and risen in young men. Combining these deaths with those registered as undetermined intent, the rates for adolescent women have remained static at 2.0 per 100 000; while for young men they increased from 3.3 to 5.7 per 100 000 before declining to 4.2 per 100 000. Conclusions: These data provide some evidence that rates of violent death in infancy and middle childhood have fallen over the past 30 years. In contrast rates in adolescence have remained static or risen over the same period.